(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2015)
Wireless sensor networks are a collection of small sensor nodes that can monitor and sense of their surroundings and sending data to a main station. The limited energy of nodes is a major challenge of sensor networks that affect the survival of the network. Thus, as yet is presented several methods to optimization of energy consumption and increasing the lifetime of a sensor network. In this paper, using fuzzy system design and system optimization by genetic algorithm is presented approach to select the best cluster head in sensor networks. Using random data set has been addressed to evaluate of fuzzy-genetic system presented in this paper and finally, MSE rate or mean error of sending the messages using proposed fuzzy system in comparison with LEACH method is calculated in select the cluster head. The results of evaluations is representative of a reduction the MSE metric in proposed method in comparison with LEACH method for select the cluster head. Reduce of MSE directly is effective on energy consumption and lifetime of wireless sensor network and can cause the reduction of energy consumption and increase the lifetime of the networks.